The effectiveness of audit committee in promoting good corporate governance in public organizations: The case of Morogoro municipal council - Kyaruzi, Flavia Johansen (Mzumbe University, 2024)
The dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for award of masters of business administration (MBA) of Mzumbe University.